2020
DOI: 10.4236/ojanes.2020.105016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guided Erector Spinae Block with Costotransverse Ligament Puncture Is More Effective than Erector Spinae Block Alone; Eight Cases for Oncologic Breast Surgery; A Brief Technical Report

Abstract: Objectives: Due to the complex breast innervation, postoperative analgesia after breast surgery is a challenge for the anesthesiologists. The erector spinae plane block (ESP) is a newly defined promising technique for this purpose. Since the description by Forero, ultrasound-guided erector spinae block (ESP) has performed for several surgeries for postoperative analgesia. Many regional methods pectoral nerve block (PECs), serratus plane block (SPB), were described in the literature for maintaining postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Only intertransverse and superior costotransverse ligaments are found in the thoracic region posing a possible obstacle [ 19 ]. Some authors reported benefits of technical refinements of ESPB such as double injection technique, multiple level injections and injecting near the costotransverse ligament in breast procedures, to improve LA diffusion into the paravertebral space [ 20 22 ]. There are no published trials on these new approaches for performing ESPB in abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Only intertransverse and superior costotransverse ligaments are found in the thoracic region posing a possible obstacle [ 19 ]. Some authors reported benefits of technical refinements of ESPB such as double injection technique, multiple level injections and injecting near the costotransverse ligament in breast procedures, to improve LA diffusion into the paravertebral space [ 20 22 ]. There are no published trials on these new approaches for performing ESPB in abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of desflurane with air -oxygen (2:1) mixture in 2 L of fresh gas flow was used for anesthesia maintenance. At the end of the surgery paracetamol 1 g and tramadol 100 mg iv were administered for providing postoperative analgesia and also ondansetron 8 mg was given for the prevention of postoperative nausea and vomiting [11] .…”
Section: Methodsmentioning
confidence: 99%